2013
DOI: 10.1007/s10433-013-0286-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of perceived health and depression with older adults’ subjective memory complaints: contrasting a specific questionnaire with general complaints questions

Abstract: The objectives of this paper were to evaluate the association of subjective memory complaints (SMC) with perceived state of health, mood and episodic memory (associative and everyday memory). We studied these areas using two different complaint assessment methods (three general questions and a validated scale). The study included 269 older adults (aged 65-87) with age-related memory changes, but without cognitive impairment. They were evaluated with Mini-cognitive Exam, Rivermead Behavioural Memory Test (a tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 57 publications
0
20
1
4
Order By: Relevance
“…Individual symptoms of depression or anxiety, or subsyndromal levels of these disorders that do not reach the threshold for diagnosis, are common in older adults and not considered exclusion criteria. Many psychiatric disorders are associated with significant cognitive complaints and even cognitive impairment (6, 55, 58, 59). Thus, including individuals with an active psychiatric disorder in studies of SCD in the context of preclinical AD would lower the specificity of the study design for AD and inflate the number of false positive cases.…”
Section: Resultsmentioning
confidence: 99%
“…Individual symptoms of depression or anxiety, or subsyndromal levels of these disorders that do not reach the threshold for diagnosis, are common in older adults and not considered exclusion criteria. Many psychiatric disorders are associated with significant cognitive complaints and even cognitive impairment (6, 55, 58, 59). Thus, including individuals with an active psychiatric disorder in studies of SCD in the context of preclinical AD would lower the specificity of the study design for AD and inflate the number of false positive cases.…”
Section: Resultsmentioning
confidence: 99%
“…García-Sevilla et al [23] also utilized MFE to assess MC performance in individuals graduated from the memory training programme at Murcia University, Spain. Montejo et al [38] evaluated the association between MC and health, humor and episodic memory perception. These authors state that a more structured tool like MFE would be strongly correlated to other variables in comparison to non-structured memory complaint open questions (OQ).…”
Section: Discussionmentioning
confidence: 99%
“…Because depressive symptoms are frequently observed in subjects with SMCs (Hohman, Beason-Held, & Resnick, 2011;Montejo et al, 2014;Sousa, Pereira, & Costa, 2015), previous studies have suggested that SMCs may constitute symptom constellations of depression (Balash et al, 2013;Balash, Mordechovich, Shabtai, Merims, & Giladi, 2010;Buckley et al, 2013;Chin, Oh, Seo, & Na, 2014;Zlatar, Moore, Palmer, Thompson, & Jeste, 2014). However, given that depressive symptoms also are known to be a risk factor for developing cognitive impairment and dementia, and the severity of depressive symptoms in older adults are well correlated with the burden of AD pathology (Lavretsky et al, 2009), the comorbidity of depressive symptoms in subjects with SMCs may play a significant role in the potential progression from SMCs to dementia.…”
Section: Introductionmentioning
confidence: 99%